2021
DOI: 10.35467/sdq/134903
|View full text |Cite
|
Sign up to set email alerts
|

The hidden curriculum in military schools

Abstract: Military education, as an integral and inseparable part of building the army as an institution, is changing its identity and tends to be becoming a place of development, changes, scientific research, quality teaching and education. Adoption of the National Curriculum Framework is creating conditions for these changes. Introduction of the military schools curriculum will inevitably lead to the hidden curriculum. In adult education (andragogy), the hidden curriculum appears in a more vigorous and influential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Professional Military Education institutions are not immune to the effects of hidden curriculum. As recent research suggests, structural and cultural inequalities have been identified in military schools (Kozina, 2015;Jansen and Kramer, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Professional Military Education institutions are not immune to the effects of hidden curriculum. As recent research suggests, structural and cultural inequalities have been identified in military schools (Kozina, 2015;Jansen and Kramer, 2019).…”
Section: Introductionmentioning
confidence: 99%